A preliminary investigation of moral reasoning and empathy after traumatic brain injury in adolescents. (July 2013) - Beauchamp, M. H.; Dooley, J. J.; Anderson, V.
Abstract Primary objective: Traumatic brain injury (TBI) sustained during childhood can affect a number of socio-cognitive skills; however, little attention has focused on the integrity of moral reasoning in the assessment of post-TBI social sequelae and the role of empathy and intelligence on moral maturity. Research design: In a quasi-experimental, cross-sectional research design, moral reasoning maturity and empathy in adolescents with mild-to-severe TBI (n = 25) were compared to typically-developing peers (n = 66). Methods and procedures: Participants were administered the So-Moral and So-Mature, tasks of socio-moral reasoning and maturity, the Index of Empathy for Children and Adolescents, the Wechsler Abbreviated Scale of Intelligence and a demographic questionnaire. Main outcomes and results: Participants with TBI had significantly lower levels of moral reasoning maturity. Further, adolescents with moderate-to-severe TBI had lower levels of empathy. Empathy correlated positively with moral reasoning abilities and, together with intellectual function, predicted a small, but significant proportion of moral reasoning outcome. Conclusions: Youth who sustained TBI during childhood have poorer moral reasoning abilities than their non-injured peers, potentially placing them at risk for poor social decision-making and socially maladaptive behaviour. This can have a significant impact on long-term social functioning.